2002
DOI: 10.1097/00003246-200203000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Dexanabinol (HU-211) in the treatment of severe closed head injury: A randomized, placebo-controlled, phase II clinical trial*

Abstract: Dexanabinol was safe and well tolerated in severe head injury. The treated patients achieved significantly better intracranial pressure/cerebral perfusion pressure control without jeopardizing blood pressure. A trend toward faster and better neurologic outcome was also observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
0
4

Year Published

2003
2003
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(78 citation statements)
references
References 18 publications
1
73
0
4
Order By: Relevance
“…Dexanabinol, a synthetic cannabinoid with antioxidant, anti-inflammatory, and antiglutamatergic properties, has also undergone phase II testing in severe TBI patients. 115 Patients receiving this drug showed improvements in initial intracranial pressure, cerebral perfusion pressure, and systolic blood pressure, with a trend towards improved six-month outcome. These results have led to a phase III trial that is currently ongoing.…”
Section: Oxidative Damagementioning
confidence: 97%
“…Dexanabinol, a synthetic cannabinoid with antioxidant, anti-inflammatory, and antiglutamatergic properties, has also undergone phase II testing in severe TBI patients. 115 Patients receiving this drug showed improvements in initial intracranial pressure, cerebral perfusion pressure, and systolic blood pressure, with a trend towards improved six-month outcome. These results have led to a phase III trial that is currently ongoing.…”
Section: Oxidative Damagementioning
confidence: 97%
“…66 -68 A phase II clinical study of 67 patients, 6-month post-injury follow-up, concluded that dexanabinol was safe and well tolerated in patients with severe TBI with significant control of ICP and cerebral perfusion pressure, and without lowering of SBP to less than 90 mmHg. 69 However, a phase III randomized placebo-controlled clinical study of dexanabinol in 861 TBI patients reported it to be safe but not efficacious. 10 Sex alters the incidence and recovery from TBI, with men experiencing more injury than women.…”
Section: Clinical Studiesmentioning
confidence: 99%
“…Treated patients achieved significantly better intracranial pressure/cerebral perfusion pressure control without jeopardizing blood pressure. A trend toward faster and better neurologic outcome was also observed [244]. Further studies (phase III randomized, placebocontrolled clinical trial) showed that dexanabinol is safe, but not efficacious in treatment of TBI [245].…”
Section: Dexanabinolmentioning
confidence: 90%